PHRASEOLOGICAL UNITS IN CONTEMPORARY FRENCH PRESS AND MEDIA: SEMANTIC, STYLISTIC, AND PRAGMATIC ASPECTS - Fazilat Mansurovna Inogamova (International Journal of Literature and Language Studies, 2026)
Abstract.This article examines phraseological units used in contemporary French press and media discourse. Their semantic, stylistic, and pragmatic characteristics are analyzed based on political, economic, and sports-related texts. The study reveals that phraseological units contribute to the dramatization and simplification of information, enhance its emotional impact, and influence the audience’s interpretation of events. The findings confirm the significant role of phraseological expressions in increasing the communicative effectiveness of contemporary media discourse.